An evaluation of the performance impact of generic group communication APIs. (5th March 2010) - Sales, L.; Teofilo, H.; Mendonca, N.C.; D'Orleans, J.; Barbosa, R.; Trinta, F.
This paper presents an evaluation of the performance impact of two generic group communication APIs, namely Hedera and jGCS, over three well-known group communication systems, namely JGroups, Spread and Appia. The evaluation compared the performance of different configurations of the three group communication systems in a local clustered environment, under different message and cluster sizes, both in standalone mode and when used as plug-ins for the two generic APIs. The results show that there are significant differences in the overhead imposed by each generic API with respect to the performance of the three group communication systems, when used in standalone mode, and that those differences are strongly related to variations in message and also to the way the generic APIs and their plug-in mechanisms are implemented. Based on those results, the paper discusses some of the circumstances upon which it would be worth implementing group communication using the investigated systems.